VOKATIVE AS AN ELEMENT OF UKRAINIAN SPEECH ETIQUETTE (SPECIAL FEATURES AND TRENDS IN THE FRAMEWORK OF THE NEWEST COMMUNICATIVE DISCOURSE) - Olena M. Turchak (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2020)
The dichotomy “language and speech” will never disappear as a part of research from linguistic studies. These two phenomena nourish and rich each other. Vocative is one of such cross-points between language and speech in Ukrainian. The paradox of the situation happens because there are certain grammar rules, also there is a rule how to use a case itself but unfortunately there are some deviations in speech too. Precisely these deviations are one of the examples of constant language and speech interaction. The relevance of the topic is due to the necessity to explore changes in the Ukrainian language associated with the use of vocative forms as a result of the new time tendency in conditions of modern communicative discourse. The purpose of the article is to consider vocative form (vocative case) formation peculiarities in the Ukrainian language in the newest communicative discourse. To achieve this goal, a descriptive method, a comparative analysis method and a classification analysis method have been used. The vocative case history in the Ukrainian language has changed greately over the last almost 100 years. These changes are being felt even now as despite the fact that vocative case has been fully functioning in the Ukrainian language paradigm since 90s of the twentieth century so far, we can still observe the wrong formation and use of form of appeal – in the nominative case instead of the vocative one. Vocative has been present in Ukrainian since ancient times. Folklore texts, where carols, generosities, spring cherries and other genres are used precisely in the vocative case, can serve its evedence. Vocative was introduced into the case paradigm of the Ukrainian language by the fourth edition of “Ukrainian spelling” and took the 7th place there. More than 25 years have passed since then but the vocative case problem has not disappeared yet, because Ukrainians are bilingual. This leads to a number of errors, since many people forget that the nominative and vocative are two different cases and each of them has its own function in the language. The nominative is the initial form which denotes the name of animated and inanimated nouns. Vocative case performs the function of the addressee`s action. In contrast to the Ukrainian language, nominative case performs two functions – nominative and appellative in the Russian language The vocative case in the Ukrainian language should be considered taking into account the category of gender, number, declination and group. According to the changes occuring in the speech, forming vocative, it is necessary to consider various options for names which exist in the language, exactly: full (official) name, abbreviated (colloquial) name or diminutive form of the name. The vocative case today is gaining momentum in speech and to a certain extent it is becoming unified. This can be seen in the case of two-word references. At the moment, appeals consisting of a common noun and a proper name as well as two common nouns are fully used only in the vocative case although another option has only been possible until recent times: a common noun in the vocative case, a proper name in the nominative; the first name is common in the vocative case, the second one is common only in the nominative case. Perhaps a similar tendency will also soon refer to appeals, which include the nominal name and surname. Time will tell.